Respuesta de la aplicación de extracto de neem en el control de radopholus similis en banano cavendish - Damián Loja, Jhon Edgar (2005)
In the place San Rafael of the parish Tenguel, canton Guayaquil and in the season of May to September of the 2005, it was realized the study of relative field to the control of nematodes of the low banana tree the system of organic production. The objectives of the work were: 1. To determine the answer of the application of the extract of neem oil in the control of Radopholus similis of the banana tree. 2. To establish the relationship of the nematodes control with the yield and quality of the fruit. 3. To carry out the economic analysis of the treatments for hectare. Six treatments were studied, three of them consisted on handmade extracts from Neem to 25%, 1, 2 and 3 l/ha; Nematron 2,0 l/ha; Biostat 250 g/ha and the absolute witness, is covering an area of cultivation of 2,16 has, in orderly parcels according to the Design of Blocks at random and with three repetitions. The aspersion was realized, selectively, in semicircle in front of the son in process of growth. The initial population of nematodes was evaluated in taken roots of six plants by sample and for parcel. After the incorporation of the products, and every 30 days they were carried out the samplings of corresponding roots. The initial population of nematodes was considered; at the 30, 60, 90 and 120 days; increment indexes and mortality or effectiveness of the control; the weigh of the cluster; the number of hands; number of fingers for hand; longitude and grade reached by the fruit to the crop. Statistical significance of the different treatments was evidenced in the control of the population of R. similis, while in the witness the population's growth was obtained, corresponding him an index of l,39 increment. The effectiveness of the products varied among 67,03 to 80,61 %, being the biggest average for Neem 3,0 l/ha. In the treated areas they were obtained that had the best weight in the cluster and number of fingers with significant differences in front of the witness. The interrelations among the nematodes population, the percentage of alive roots and the weight of the cluster, correlated significantly.